Principles of addiction medicine : the essentials - Cavacuiti, Chris (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Principles of Addiction Medicine: The Essentials is a compact and portable distillation of the American Society of Addiction Medicine's flagship text, Principles of Addiction Medicine. This handbook present the clinically essential points from the larger text in an easy-to-follow outlined and bulleted format. Each chapter follows a template with structured headings such as pharmacokinetics, pharmacodynamics, therapeutic uses, effects, liability, and withdrawal. Principles of Addiction Medicine: The Essentials is an excellent reference for a wide variety of addiction medicine professionals, including psychiatrists, psychologists, psychiatric nurses, social workers, internal medicine/primary care physicians, and substance abuse counselors"--Provided by publisher.
section 1. Basic science and core concepts -- section 2. Pharmacology -- section 3. Diagnosis, assessment, and early intervention -- section 4. Overview of addiction treatment -- section 5. Special issues in addiction medicine -- section 6. Management of intoxication and withdrawal -- section 7. Pharmacologic interventions -- section 8. Behavioral interventions -- section 9. Mutual help, twelve-step, and other recovery programs -- section 10. Medical disorders and complications of addiction -- section 11. Co-occurring addiction and psychiatric disorders -- section 12. Pain and addiction -- section 13. Children and adolescents -- section 14. Ethical, legal, and liability issues in addiction practice.
Abridgement of: Principles of addiction medicine. 4th edition c2009.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Substance abuse -- Handbooks, manuals, etc; Electronic books